Use of conjunctions in argumentative essay by ESL undergraduates / Nuruladilah Mohamed - Mohamed, Nuruladilah (2016)
This study examines one aspect that contributes to writing quality in argumentative essay which is the usage of cohesive devices, specifically the usage of conjunctions. Cohesion is regarded as an essential textual component both in creating organized texts and interpreting the content that are comprehensible to readers. The objectives of the study are to determine the frequency of conjunctions used by Malaysian ESL undergraduates in their academic essays, to identify the semantic categories of conjunctions mostly used by the learners and to identify which category of conjunctions is the most problematic to the ESL learners. The data of this study comprised of 50 argumentative essays on a specific topic written by 50 Universiti Teknologi Mara (UiTM) undergraduates and semi-structured interviews were also carried out to elicit information. Findings reveal that there are appropriate and inappropriate applications of conjunctions in the essay due to lack of exposure to different categories of conjunctions and difficulties to use other conjunctions that share similar meaning.